2015
DOI: 10.1038/oncsis.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutations and monoallelic activation of TERT in cancer

Abstract: Here we report that promoter mutations in telomerase (TERT), the most common noncoding mutations in cancer, give rise to monoallelic expression of TERT. Through deep RNA sequencing, we find that TERT activation in human cancer cell lines can occur in either mono- or biallelic manner. Without exception, hotspot TERT promoter mutations lead to the re-expression of only one allele, accounting for approximately half of the observed cases of monoallelic TERT expression. Furthermore, we show that monoallelic TERT ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 19 publications
10
103
0
Order By: Relevance
“…Some cancer cell lines show monoallelic expression (MAE) of TERT even in the absence of promoter mutations (Huang et al, 2015). This phenotype suggested that the epigenetic conditions that facilitate TERT expression in these cells might be distinct from those with wt promoters that express TERT biallelically or cancers with promoter mutations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some cancer cell lines show monoallelic expression (MAE) of TERT even in the absence of promoter mutations (Huang et al, 2015). This phenotype suggested that the epigenetic conditions that facilitate TERT expression in these cells might be distinct from those with wt promoters that express TERT biallelically or cancers with promoter mutations.…”
Section: Resultsmentioning
confidence: 99%
“…(B) CCLE WT, wild-type at the TERT promoter. MUT, −124 or −146 TERT promoter mutants, mono_WT, cell lines without known TERT promoter mutations exhibiting monoallelic TERT expression (Huang et al 2015). …”
Section: Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that TERT promoter mutations could be potential mechanisms for TERT reactivation in cancer cells. In more recent studies, investigators found that two highly recurrent point mutations (G228T and G250T) in the TERT promoter might be among the fundamental mechanisms underlying telomerase reactivation/expression in several types of human cancers[149,151-154]. …”
Section: Somatic Mutations In Hccmentioning
confidence: 99%